COMPARATIVE ANALYSIS OF CONSUMER BEHAVIOR BETWEEN COMPULSIVE BUYING AND IMPULSIVE BUYING BASED ON MONEY ATTITUDES AND DEMOGRAPHIC IN MANADO - Kolibu, Relinton Jeremia; Tumbuan, Willem J. F. A.; Tasik, Hizkia H.D (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: There are two things which influence consumer buying behavior, namely compulsive and impulsive buying behaviors. The purpose of this research is to find out the difference between consumer behaviors of compulsive and impulsive buyer based on power prestige, retention time, distrust, anxiety, and demographic factors in Manado. This is a comparative research, using Independent Sample T-Test and Multiple Linear Regressions as analytical tools. On the other hand, the data collected in a survey on 200 respondents. The result shows that there is a significant difference based on power prestige, retention time, and distrust but there is no significant difference on anxiety between compulsive and impulsive buyer in Manado. Meanwhile the result of multiple linear regressions test based on impulsive buying shows that only anxiety that has no significant impact on impulsive buying. For compulsive buying, the result shows that power prestige, anxiety, age education, occupation, and income significantly affect compulsive buying, but retention time and distrust have no significant impact on compulsive buying. Consumers that buy impulsively have to start making a plan or make list of things that they want to buy before they go into the shopping centers. Consumers with compulsive buying behavior need to gain control over their shopping decisions.Keywords: comparative analysis, compulsive buying, impulsive buying, money attitudes, age, education, occupation, income.